Basic concepts in environmental biotechnology - Sharma, Neetu ;Sodhi,Abhinashi Singh;Batra,Navneet (New York CRC Press, 2022)
"The book includes current and emerging concepts in the area of environmental biotechnology like pollution- source, control and measurement, bioremediation, biofuels, biosensors, conservation biotechnology etc. The book includes recent studies and innovations made in this field and incorporates case studies to help in understanding the concepts"